Monetary policy and its transmission in a globalised world - Michele Ca' Zorzi; Luca Dedola; Georgios Georgiadis; Marek Jarocinski; Livio Stracca; Georg Strasser (European Central Bank (ECB), 2020)
This paper estimates and compares the international transmission of European Central Bank (ECB) and Federal Reserve System monetary policy in a unified and methodologically consistent framework. It identifies pure monetary policy shocks by purging them of the bias stemming from contemporaneous central bank information effects. The results suggest that there is a hierarchy in the global spillovers from ECB and Federal Reserve monetary policy: while the spillovers to consumer prices are relatively small in both directions, Federal Reserve monetary policy shocks have a larger impact on euro area financial markets and real activity. Federal Reserve monetary policy also has a significantly larger impact than ECB monetary policy on real and financial variables in the rest of the world.
Keywords: E44; E52; F3; E58; F42; 330; monetary policy spillovers; monetary policy shocks; international monetary policy coordination; international shock transmission